2019
DOI: 10.3389/fenvs.2019.00008
|View full text |Cite
|
Sign up to set email alerts
|

The Development of the Water-Energy-Food Nexus as a Framework for Achieving Resource Security: A Review

Abstract: This paper presents a study of the evolution of the water-energy-food (WEF) nexus since its rise to prominence in policy and development discourses in 2011. Drawing from an extensive review of published literature, the paper presents various interpretations of the concept while also considering the novelty of the WEF nexus. The challenge of integrating and optimising the components of this multi-centric nexus is examined, with four case studies being presented. Various criticisms levelled at the WEF nexus, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
143
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(151 citation statements)
references
References 48 publications
0
143
0
8
Order By: Relevance
“…Recent studies have made contrasting reports about when and how the nexus within the sustainable management discourse emerged (Siddiqi and Anadon, 2011;Conway et al, 2011;Muller, 2015;Pahl-Wostl et al, 2018;Simpson and Jewitt, 2019). While initial studies around the nexus are mostly limited to water and energy interactions and in some instance incorporate food production, Siddiqi and Anadon (2011) suggested that the need to acknowledge and understand the WE nexus was recognised as early as 1994.…”
Section: Contextual Developments On Wecc Nexusmentioning
confidence: 99%
“…Recent studies have made contrasting reports about when and how the nexus within the sustainable management discourse emerged (Siddiqi and Anadon, 2011;Conway et al, 2011;Muller, 2015;Pahl-Wostl et al, 2018;Simpson and Jewitt, 2019). While initial studies around the nexus are mostly limited to water and energy interactions and in some instance incorporate food production, Siddiqi and Anadon (2011) suggested that the need to acknowledge and understand the WE nexus was recognised as early as 1994.…”
Section: Contextual Developments On Wecc Nexusmentioning
confidence: 99%
“…In the context of global environmental change and efforts to achieve the United Nations Sustainable Development Goals, the water-energy-food (WEF) nexus framework is increasingly promoted as a means to integrate across systems and solution, identify and address risks, and ultimately contribute to sustainability (Bazilian et al, 2011;Hoff, 2011;Hussey and Pittock, 2012;Boas et al, 2016;Benson et al, 2017;Weitz et al, 2017a;Simpson and Jewitt, 2019). Nexus research explicitly connects human and natural systems, in order to provide a more complete picture about the causes and consequences of change.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, according to the World Economic Forum (WEF), it was the first year in which an environmental danger, specifically the failure to mitigate and adapt to climate change, ranked above weapons of mass destruction, water shortage, and energy resource prices (WEF, 2018). As can be seen, environmental concerns have been a priority for the WEF in recent years (Obersteiner et al, 2018;Simpson and Jewitt, 2019). Because of this, state parties to the Paris Agreement committed to reducing their greenhouse gas (GHG) emissions, with the aim of limiting global warming to well-below 2 • C above pre-industrial levels, and to pursue efforts to keeping the increase down to 1.5 • C (Karmalkar and Bradley, 2017;Nikulin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%